Navigatebot: Voice-based AI chatbot for UiTM Tapah / Nur Aimi Aziah Azizul - Azizul, Nur Aimi Aziah (2022)
University Technology MARA (UiTM) located in Tapah, Perak is a campus with buildings, divisions, offices, and facilities that spread over its wide zone may possibly intimidate its guests to find their locations. It can be a difficult task for a person to navigate certain places in a situation which is new or unfamiliar for the individual. Additionally, students, staff and visitors may have questions which required the individual to find a few places around the campus. The person that was being asked might also have difficulties with giving direction and this turned out to be time consuming. The aim of this project is to create a platform where this problem can be solved through chatbots.